Care of the person with mental problems, challenge of ethics towards the holistic nursing approach in a level III hospital de Lambayeque - Rodríguez Olivos, Gina Salome (2022)
Objective: To describe and analyze the care of the person with mental problems as a challenge of ethics with a holistic nursing approach in a Level III Hospital, in the department of Lambayeque. Method: Research with qualitative, descriptive exploratory sketch. 8 nurses of the hospital described with informed consent were involved; the sampling was non-probabilistic and the sample was achieved by saturation and redundancy. A semi-structured interview was used to collect the information, validated by the judgment of three experts and a pilot study. The data obtained were processed by thematic content analysis with endorsement of ethical principles and scientific rigor Main results: Three categories emerged: Safety and protection of the life of the mentally ill patient as a whole. Ethical practices and harmonization of care for the mentally ill person. Profiling with training to nurture the human integrity of the mentally ill person. Overall conclusion: Nurses working in the psychiatry service are discerning about their ethical practices and reasoning about how to harmonize care to get not only to take care of the patient's body but also his mind and spirit, achieved with years of experience, with attention to their integral needs from their hygiene to their sleep, knowing how to guide them in true spirituality, without neglecting the family that sometimes is confused and full of problems.